Some issues on the integration of renewable energy with existing power distribution network - Tan, Peng Wee. (2011)
Traditional generating systems such as Steam (Coal) Turbines produce pollution that incurs high environmental costs. In addition, the large demand for energy in the world today will inevitably deplete the supply of non-renewable sources such as coal. Hence, world leaders are increasingly searching for alternatives to traditional generating systems. Some of these alternatives include solar energy systems, wind energy systems and hydropower systems. These systems make use of renewable sources, which will never be depleted. These systems also produce little to no harmful emissions hence making them more attractive alternatives.